2020
DOI: 10.26434/chemrxiv.12022779.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Photoinduced Intersystem Crossing in DNA Oxidative Lesions and Epigenetic Intermediates

Abstract: The propensity of 5-formyluracil and 5-formylcytosine, i.e. oxidative lesions and epigenetic intermediates, in acting as intrinsic DNA photosensitizers is unraveled by using a combination of molecular modeling, simulation and spectroscopy. Exploration of potential energy surfaces and non-adiabatic dynamics confirm a higher intersystem crossing rate for 5-formyluracil, whereas the kinetic models evidence different equilibria in the excited states for both compounds

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Evidence was provided for thymine photodimerization when 5‐forU is embedded into a ds‐DNA structure. Similarly, 5‐formylcytosine (5‐ForC) that can be generated in cellular DNA by radical oxidation reactions (238) and also enzymatically as an epigenetic mark by ten‐eleven translocation dioxygenases (109) exhibits the ability to photosensitize the formation of CPDs, although less efficiently than 5‐ForU (239,240). The absorbance of 5‐forC that essentially concerns the UVB domain is less redshifted than that of 5‐ForU, thus making the oxidized cytosine a rather poor UVA photosensitizer.…”
Section: Triplet–triplet Energy Transfermentioning
confidence: 99%
“…Evidence was provided for thymine photodimerization when 5‐forU is embedded into a ds‐DNA structure. Similarly, 5‐formylcytosine (5‐ForC) that can be generated in cellular DNA by radical oxidation reactions (238) and also enzymatically as an epigenetic mark by ten‐eleven translocation dioxygenases (109) exhibits the ability to photosensitize the formation of CPDs, although less efficiently than 5‐ForU (239,240). The absorbance of 5‐forC that essentially concerns the UVB domain is less redshifted than that of 5‐ForU, thus making the oxidized cytosine a rather poor UVA photosensitizer.…”
Section: Triplet–triplet Energy Transfermentioning
confidence: 99%
“…This process can also be facilitated by the additional stabilization of thymine triplet 3 T due to π-stacking, and the related multichromophoric coupling in the DNA helical structure. Thymine photochemistry has been explored as early as 1960s (11), but the presence of 3 T (12) has triggered renewed attention, notably for delineating the mechanism of triplet-triplet energy transfer with external photosensitizers (13), or with modified nucleobases and oxidative lesions recognized as Trojan Horses (9,14). It has also been shown that the population of 3 T opens rather efficient photochemical channels for dimerization (15,16), even if there is no experimental evidences for the formation of 64-PP mediated by 3 T. The energy of 3 T in a DNA strand has been inferred experimentally by Bosca et al by assessing the energy transfer efficiency of different photosensitizers, such as norfloxacin and its N4'-acetyl derivative, whose energies are precisely known (17).…”
Section: Introductionmentioning
confidence: 99%
“…Since other species ( 2 NO, 3 O, 3 S, and 2 H) could also produce analogous reactions 12,19,53 , we accurately determined their reactivity with cis-OSSO (Supplementary Table 6 and Supplementary Figs. [28][29][30][31][32][33][34][35] to update previous estimations for the rate of these reactions.…”
Section: So Deoxygenation Reactionsmentioning
confidence: 99%
“…In this work, we identify the main photochemical routes of 1 (SO) 2 isomers by accurately simulating the gas-phase conditions of the Venus atmosphere through non-adiabatic molecular dynamics (NAMD) [25][26][27][28][29][30][31] , a well-established state-of-the-art methodology [32][33][34][35][36][37][38][39][40][41][42] , especially in combination with multiconfigurational quantum chemistry [43][44][45][46][47] . For HOSO 48,49 and HOSO 2 50,51 radical photochemistry, NAMD has recently demonstrated that the ejection of OH is the main photodissociation channel for both systems in Earth's atmosphere 24,52 .…”
mentioning
confidence: 99%